THE EFFECT OF LGBT’S CONTENT IN TIK TOK ON THE ACCEPTANCE OF LGBT BY COLLEGE STUDENTS IN A CAMPUS ENVIRONMENT - Freza Nisfi Romadlon; Ginar Ayuningtyas; Renny Sundayani (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2022)
As a platform, TikTok is more open to people positing queer content. For example, seeing two men embracing each other, doing make-up on a trans person, or else. Although there are questions about censorship of LGBTQ content, the videos in that space are supportive and sometimes surprisingly confessional.The present study aims to describe the effects of gay content on TikTok social media on students’ acceptance about the presence of gays in the campus environment. The research method used is descriptive quantitative to explain a causal relationship of two variables by collecting data that has been distributed from 100 respondents who were randomly selected using a multistage random sampling. The results of present research show that despite feeling anxious about the existence of gay contents in TikTok social media, the participants accept the existence of gays due to several factors such as the existing culture in those places and peer groups. In addition, there is a relationship between the influence of social media content and the level of self-acceptance with the direction of the relationship being unidirectional because the correlation is positive. Furthermore, the level of influence of social media content correlates with the level of acceptance of gay identity among students.